Pendampingan UMKM dalam Mengembangkan Strategi Pemasaran Produk pada Media Sosial dan Platform E-Commerce - Bachrul Ulum; Mohammad Hasib; Andreas Andrie Djatmiko; Dwi Agustina Rahayu; Pangki Suseno (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The advent of the Industrial Revolution 5.0 has had a profound impact on the global landscape, including Indonesia. Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the national economy, but a considerable number of them have yet to leverage e-marketplaces and social media as marketing tools. This has resulted in a digital chasm between MSMEs and larger corporations. Thus, it is imperative to provide adequate assistance and training to MSMEs to enable them to harness digital technology and enhance their competitiveness in the e-commerce market. The Participatory Action Research (PAR) method is employed, which involves training, account creation practice, and mentoring for MSMEs. The training is conducted in three phases, namely preparation, implementation, and evaluation. As a result of community service activities, MSMEs need to innovate their products and employ digital marketing strategies through platforms such as marketplaces and social media. Diligent preparation is essential to enable MSMEs to adapt to these changes and bridge the digital divide. Community service initiatives in Kedondong Village strive to encourage MSMEs to embrace marketing strategies through social media and e-commerce platforms as a means to increase revenue and expand businesses in the fiercely competitive digital era.